Evaluasi Sistem Reward Non-Finansial Dalam Memotivasi Karyawan Milenial Pada Universitas Almuslim - Afriana Afriana; Azka Rizkina; Emi Safrina; Muammar Qadafi; Yusrawati Yusrawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to evaluate the Non-Financial Reward System in Motivating Millennial Employees at Almuslim University. Millennial generation employees are employees born between 1981-1996 who are now starting to dominate the world of work. This study uses a quantitative descriptive approach with a survey method. With the aim of evaluating the effectiveness of the non-financial reward system in increasing the work motivation of millennial employees at Almuslim University. The results of the study explain that there are 46 millennial employees in the Almuslim University environment, a general overview is obtained that female participation in this study is more dominant than male, where the percentage of women is 67.4 percent and men are only 32.6 percent. In terms of age, the majority of respondents are over 35 years old (60.9 percent), while those aged between 31-35 years are 26.1 percent, and the rest are 25-30 years old by 13 percent. Based on the results of the simple linear regression test, the significance value obtained is 0.000 which is smaller than 0.05. This indicates that non-financial rewards have a positive and significant influence on the work motivation of millennial employees at Almuslim University. This means that the better the non-financial reward system implemented, the higher the level of work motivation experienced by employees. The regression coefficient of 0.678 indicates that every one-unit increase in the non-financial reward variable can increase work motivation by 0.678 units.